Interleukin-18 Expression Increases in the Aorta and Plasma of Patients with Acute Aortic Dissection - Haiying Hu; Guangtai Zhang; Huanli Hu; Wenjing Liu; Jixiang Liu; Shuanli Xin; Xiufeng Zhao; Liying Han; Liping Duan; Xinshun Huang; Chao Chang (Mediators of Inflammation)
Background. Interleukin- (IL-) 18 is a proinflammatory cytokine related to cardiovascular diseases, including hypertension and atherosclerosis. This study is aimed at determining whether IL-18 is related to aortic dissection (AD) and identifying the underlying mechanisms. Methods. IL-18 expression in human aorta samples from AD (n=8) and non-AD (NAD, n=7) patients was measured. In addition, the IL-18, IL-6, interferon- (IFN-) γ, and IL-18-binding protein (IL-18BP) concentrations in plasma samples collected from the NAD and AD patients were detected. The effects of IL-18 on macrophage differentiation and smooth muscle cell (SMC) apoptosis were investigated in vitro. Results. IL-18 expression was significantly increased in the aorta samples from the AD patients compared with those from the NAD patients, especially in the torn section. Aortic IL-18 was mainly derived from macrophages and also partly derived from CD4+ T lymphocytes and vascular SMCs. Plasma IL-18, IFN-γ, and IL-6 levels were significantly higher in the AD group than in the NAD group, and the IL-18 levels were positively correlated with the IFN-γ and IL-6 levels. In addition, plasma IL-18BP and free IL-18 levels were also elevated in the AD group. Linear regression analysis showed that the IL-18 level was independently associated with the presence of AD. In addition, anti-mouse IL-18-neutralizing monoclonal antibodies (anti-IL-18 nAb) inhibited angiotensin II-induced M1 macrophage differentiation and SMC apoptosis in vitro. Conclusion. IL-18 may participate in AD by regulating macrophage differentiation and macrophage-induced SMC apoptosis.